Efforts to Increase Knowledge Through Health Education on Breast Self-Examination Skills in Women of Childbearing Age in Sumber Jaya Village, Kampung Melayu District, Bengkulu City in 2022 - Nispi Yulyana; Elly Wahyuni; Wewet Savitri; Suci Solihat (CV Media Inti Teknologi, 2022)
Data from the Bengkulu Provincial Health Office, Bengkulu Province is included in 10 provinces that have low coverage in clinical breast examination (SADANIS) and IVA examinations below 5%, Based on data from the Bengkulu City Health Office in 2020 of 62,160 WUS SADANIS examinations and IVA tests only 1967 person.The working area of ​​the Padang Serai Health Center, Kampung Melayu Subdistrict, is the highest area that has the highest incidence of suspicion and tumors or breast lumps in Bengkulu City. The working area of ​​the Padang Serai Health Center, Kampung Melayu Subdistrict, has 3 sub-districts, namely Sumber Jaya sub-district, Padang Serai sub-district and Teluk Sepang sub-district. The Padang Serai Health Center Working Area, Kampung Melayu District has 3,356 WUS, of which 331 people were examined.For suspicious data12 people had breast cancer and 13 people had tumors or breast lumps. The incidence of breast cancer is in Sumber Jaya Village.Adolescent reproductive health problems in Indonesia do not receive enough attention because knowledge about early detection and breast self-care skills have not been socialized properly. Because of that, there is a need for awareness and participation from various related agencies to be able to provide knowledge as early as possible about the importance of early detection of breast cancer and breast self-care skills. This can be done in real terms through counseling efforts. In this community service activity there will be socialization, counseling, mentoring and group formation using the peer group method at WUS in Sumber Jaya Village, Kampung Melayu District.